Profiles and Predictive Values of Interleukin-6 in Aortic Dissection: a Review - Yuan,Shi-Min (2019)
Abstract Aortic dissection (AD) has been recognized to be associated with an inflammatory process. Clinical observations demonstrated that patients with AD had an elevated interleukin (IL)-6 level in comparison to hypertensive or healthy controls. Adverse events such as acute lung injury, postimplantation syndrome, and death are associated with an elevated IL-6 level. Thus, circulating IL-6 could be a reliable biomarker for the diagnosis of AD and for the eveluation of the therapeutic outcomes and the prognosis of AD patients. Therapeutic interventions aiming at attenuating the inflammatory status by IL-6 neutralization could effectively decrease the IL-6 level and thus reverse the progression of the disorder of AD patient. Endovascular aortic repair can effectively control the inflammatory cytokines. Selective antegrade cerebral perfusion with deep hypothermic circulatory arrest during aortic arch replacement shows better neuroprotectve effect with an improved IL-6 level of the cerebrospinal fluid. These results facilitate the understanding of the etiology of AD and guide the directions for the treatment of acute AD in the future. More effective therapeutic agents developed based on the theories of IL-6 signaling involved in the mechasims of AD are anticipated.